Phytoplankton community structure is influenced by seabird guano enrichment in the Southern Ocean. (15th May 2017) - Shatova, O.A.; Wing, S.R.; Hoffmann, L.J.; Wing, L.C.; Gault-Ringold, M.
Abstract: Phytoplankton biomass, productivity and community structure are strongly influenced by differences in nutrient concentrations among oceanographic water masses. Changes in community composition, particularly in the distribution of cell sizes, can result in dramatic changes in the energetics of pelagic food webs and ecosystem function in terms of biogeochemical cycling and carbon sequestration. Here we examine responses of natural phytoplankton communities from four major water masses in the Southern Ocean to enrichment from seabird guano, a concentrated source of bioactive metals (Mn, Fe, Co, Ni, Cu, Zn) and macronutrients (N, P), in a series of incubation experiments. Phytoplankton communities from sub-tropical water, modified sub-tropical water from the Snares Island wake, sub-Antarctic water and Antarctic water from the Ross Sea, each showed dramatic changes in community structure following additions of seabird guano. We observed particularly high growth of prymnesiophytes in response to the guano-derived nutrients within sub-Antarctic and sub-tropical frontal zones, resulting in communities dominated by larger cell sizes than in control incubations. Community changes within treatments enriched with guano were distinct, and in most cases more extensive, than those observed for treatments with additions of macronutrients (N, P) or iron (Fe) alone. These results provide the first empirical evidence that seabird guano enrichment can drive significant changes in the structure and composition of natural phytoplankton communities. Our findings have important implications for understanding the consequences of accumulation of bioactive metals and macronutrients within food webs and the role of seabirds as nutrient vectors within the Southern Ocean ecosystem. Graphical abstract: Highlights: Seabird guano contains a balanced compliment of macronutrients and bioactive metals to support phytoplankton growth. Additions of seabird guano to subTropical, subAntarctic, subAntarctic island and Antarctic watermasses resulted in dramatic increases in biomass and changes in community structure. Phytoplankton communities from subTropical, subAntarctic island and subAntarctic watermasses shifted to community structure with more large-celled species following additions of guano. Community changes within guano treatments were distinct from those observed for treatments with additions of macronutrients (N, P) or iron (Fe) alone. Our findings have important implications for understanding accumulation of nutrients within food webs and the role of seabirds as nutrient vectors within the Southern Ocean ecosystem.